Analisis Pengaruh Manajemen Risiko Terhadap Kinerja Keuangan Perbankan yang Terdaftar di BEI - Bhirgita Christine Dwi Yanti; Adi Irawan Setiyanto (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2021)
Banks have a strategic role in national economic development. The large number of funds managed by banks causes the risks faced are also very large. Very supportive if the risk affects the bank's performance, therefore banks are required to implement risk management. After being selected using the purposive sampling method, the sample banks were 21 banks. Tests carried out with multiple regression analysis show that bad loans and operating expenses on operating income negatively affect asset returns. In contrast to the loan to deposit ratio which does not affect the return on assets. Based on the results of this study, it is necessary to optimize credit and operational risks which are considered capable of maintaining the stability of bank profitability.